2020
DOI: 10.1038/s41467-019-13988-4
|View full text |Cite
|
Sign up to set email alerts
|

Photons as a 21st century reagent

Abstract: A pharmaceutical industry viewpoint on how the fundamental laws of photochemistry are used to identify the parameters required to implement photochemistry from lab to scale. Parameters such as photon stoichiometry and light intensity are highlighted within to inform future publications. Photochemistry employs photons to drive chemical transformations. Traditional approaches rely on the direct excitation of bonds with light 1,2. In contrast, photoredox catalysis uses a photosensitizer to facilitate electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
149
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 14 publications
1
149
0
3
Order By: Relevance
“…They discovered that the choice of the PS impacted the selective formation of mono-vs difluorinated products at the benzylic position; 9-fluorenone affords benzylic monofluorination and xanthone affords benzylic difluorination (Scheme 5). Importantly, this metal-free direct C-H fluorination proceeded without the need for any specialized photochemical equipment; under visible-light irradiation by a household (19 W) compact fluorescent light (CFL) bulb (emitting variable wavelengths in the range of ≈365-625 nm) [195] and under mild conditions. Control reactions revealed that both the PS and light were essential for the reaction to occur.…”
Section: Benzylic C-h Fluorinationmentioning
confidence: 99%
“…They discovered that the choice of the PS impacted the selective formation of mono-vs difluorinated products at the benzylic position; 9-fluorenone affords benzylic monofluorination and xanthone affords benzylic difluorination (Scheme 5). Importantly, this metal-free direct C-H fluorination proceeded without the need for any specialized photochemical equipment; under visible-light irradiation by a household (19 W) compact fluorescent light (CFL) bulb (emitting variable wavelengths in the range of ≈365-625 nm) [195] and under mild conditions. Control reactions revealed that both the PS and light were essential for the reaction to occur.…”
Section: Benzylic C-h Fluorinationmentioning
confidence: 99%
“…Light as a reagent and tool [1][2][3][4][5][6][7][8][9][10][11] has received gained interest because it interdisciplinary connects different fields of chemistry, biology and physics resulting in emerging applications related to display technologies based on holography [12] , 2D [13][14] and 3D printing [15][16][17][18] , photopharmacology [19] , dentistry [20] or environmental sciences to clean water and/or air from microbial ballast [21] -just to name a few emerging applications. It requires knowledge about the properties of the excited state such as lifetime, redox potentials and excitation energy to design systems working with appropriate light sources such as LEDs or lasers resulting in generation of initiating radicals or conjugate acid to initiate radical or cationic polymerization, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The narrower spectra, while providing many benefits and likely reducing the occurrence of side reactions, also facilitate that other factors become more important. Notably, an exact description of the photoflow setup is now crucial to ensure reproducible experiments [20,21].…”
Section: Introductionmentioning
confidence: 99%